The current ecological state of mountain ram (Ovis ammon collium) of population of GNPP «Buyratau» - Turlybekova, G.K. (Fundamental and Experimental Biology, 2017)
This article in is showed the ecological features of mountain sheep’s (Оvis ammon collium) population of «Buyratau», a state national nature park. It is belong to rare and endangered category from the Red book. Area of existence of animals is local. It is one of fivemountain sheep’s subspecies, which exist in Kazakhstan. Argali use winter and summer pastures, with which their seasonal movements. Daily activity changes at seasons of year and depends onf factors as: temperature of air, light intensity,air humidity, the frequency of rains and snowfalls, influence of sanguivorousinsects and physiological state of animals. Food allowance of argali includes 87 species of plants. Today the number of population of argali in «Buyratau» depend of several complex of factors,: anthropogenic and natural factors. The most important natural factor is death from wolves. Strategy creation of biological defence, reproduction and rational use is impossible without detailed knowledge of the animal’s ecology and of factors that influence on its population in specific conditions which correspond to objectives of Convention on Biological Diversity, which was approved by the government of Republic of Kazakhstan.